PHYSICAL STUDIES OF PHOSPHOLIPIDS : III. Electron Microscope Studies of Some Pure Fully Saturated 2,3-Diacyl-DL-Phosphatidyl-Ethanolamines and Phosphatidyl-Cholines - Chapman, D. (The Rockefeller University Press, 1966)
On heating pure, fully saturated 2,3-diacyl-DL-phosphatidyl-ethanolamines and 2,3-diacylphosphatidyl-cholines (lecithins) in water to the transition temperature at which large endothermic heat changes occur, they are observed, by light microscopy, to form myelin figures. This result is discussed in terms of the large difference in the transition temperature for "melting" of the hydrocarbon chains of unsaturated and saturated phospholipids and is illustrated by means of differential thermal analysis (D.T.A.) curves. These structures have been examined by electron microscopy after negative staining and after reaction with osmium tetroxide. Typical phospholipid lamella structures are seen in the phosphatidylcholines after negative staining, and in the phosphatidyl-ethanolamines after both negative staining and osmium fixation. The distances across these lamellae have been measured. Some preliminary investigations of the nature of the osmium tetroxide reaction with the phosphatidyl-ethanolamines have been made.